Adaptive Fuzzy Proportional Integral Sliding Mode Control for Two-Tank Interacting System - Thanh Tung Pham; Chi-Ngon Nguyen (Journal of Engineering and Technological Sciences, 2022)
This paper presents an adaptive fuzzy proportional integral sliding mode control (AFPISMC) for two-tank interacting system (TTIS). In order to maintain the desired liquid level of the TTIS and meet the reference values for attenuated chattering problems, this paper proposes a combination of a sliding mode control (SMC) with a proportional integral (PI) sliding surface and a fuzzy inference system. Fuzzy logic and the universal approximation theorem of fuzzy systems are used to approximate the uncertain function in the PISMC. The stability of the control system is proved by the Lyapunov theory. The simulation results of the proposed method in MATLAB/Simulink were compared to a fuzzy control, a sliding mode control with conditional integrals, a fuzzy-PID control, and a conventional PID control. The comparison results showed that the proposed controller was most effective when the rising time reached 0.2375 s, the percent of overshoot was 0%, the steady state error converged to zero, the settling time was 0.4612 s, and chattering was reduced.